Optimization of Type 2 Diabetes Patient Assistance Through Enhanced Telecoaching Capacity for Primary Healthcare Nurses in Kendari City - Saltar, Laode; Said, Muhammad Sulkifly; Bayu, Wisnu Catur (Jurnal Kreativitas Pengabdian Kepada Masyarakat (PKM), 2025)
ABSTRACT Diabetes Mellitus (DM) is a health problem that requires a multidisciplinary approach, including the important role of community health center nurses. Telecoaching conducted by nurses has proven effective in improving glycemic levels in DM patients. This community service program aimed to enhance the capacity of primary healthcare center (puskesmas) nurses in providing telecoaching to Type 2 Diabetes Mellitus (DM) patients in the coastal areas of Kendari City. The program was designed to address the limitations in nurses' knowledge and skills while increasing the intensity of remote patient support for DM. A total of 10 primary healthcare nurses participated in the training, which covered telecoaching techniques, motivational interviewing, and the use of the Diabetes Mellitus Patient Health Assistance Application (DMPHAA). Evaluations assessed improvements in nurses' knowledge and skills, as well as reductions in the fasting blood glucose levels of DM patients. The results showed a significant increase in nurses' knowledge of telecoaching by 40.30% and a 52.76% improvement in telecoaching skills after the intervention. In addition, there was a 20.61% reduction in the fasting blood glucose levels of DM patients, demonstrating the program's effectiveness in helping patients manage their diabetes. Statistical tests showed significant results for all three variables with p<0.05. This program demonstrated that telecoaching can be an effective solution for providing remote healthcare services, especially in areas with limited access. It is recommended that the sustainability of this program is integrated into the services of primary healthcare centers to improve diabetes management in remote regions. Keywords: Telecoaching, Diabetes Mellitus, Primary Healthcare Nurses, Blood Glucose, Community Service